Scheduling in the Aeronautical Industry Using a Mixed Integer Linear Problem Formulation - Borreguero, T.; García, A.; Ortega, M. (Procedia engineering, 2015)
Scheduling is becoming much more important in every industry. At the same time, scheduling problems have been the subject of continuous research since the early days of operations research. However, the standard resource constraint scheduling problem (RCSP) usually does not cover all the characteristics of real world problems. In this work, we present an Event Based Mixed Integer Linear Problem (MILP) formulation for a Multimode Resource Constraint Problem (MRCSP) of direct application for some industries, as aerospace final assembly lines. Taking as a starting point one of the last MILP formulations for standard RCSP, its contribution is to provide a formulation which covers the multimode case and more general temporal constraints than the ones usually referred to in the literature. This publication focuses on the computational results, their relevance and their impact for a future extension to solving real world instances.